Upregulation of hypothalamic POMC neurons after biliary diversion in GK rats - Zhou, Shengnan; Chen, Weijie; Bai, Xuesong; Chen, Jiemin; Xu, Qiang; Dong, Liangbo; Chen, Wei; Qu, Qiang; He, Xiaodong (Frontiers in Endocrinology, 2022)
Background: Bile acids are important signaling molecules that might activate hypothalamic neurons. This study aimed to investigate possible changes in hypothalamic pro-opiomelanocortin (POMC) neurons after biliary diversion in diabetic rats. Methods: Ten GK rats were randomly divided into the biliary diversion (BD) and sham groups. The glucose metabolism, hypothalamic POMC expression, serum bile acid profiles, and ileal bile acid-specific receptors of the two groups were analyzed. Results: Biliary diversion improved blood glucose (P = 0.001) and glucose tolerance (P = 0.001). RNA-Seq of the hypothalamus showed significantly upregulated expression of the POMC gene (log2-fold change = 4.1, P < 0.001), which also showed increased expression at the protein (P = 0.030) and mRNA (P = 0.004) levels. The POMC-derived neuropeptide α-melanocyte stimulating hormone (α-MSH) was also increased in the hypothalamus (2.21 ± 0.11 ng/g, P = 0.006). In addition, increased taurocholic acid (TCA) (108.05 ± 20.62 ng/mL, P = 0.003) and taurodeoxycholic acid (TDCA) (45.58 ± 2.74 ng/mL, P < 0.001) were found in the BD group and induced the enhanced secretion of fibroblast growth factor-15 (FGF15, 74.28 ± 3.44 pg/ml, P = 0.001) by activating farnesoid X receptor (FXR) that was over-expressed in the ileum. Conclusions: Hypothalamic POMC neurons were upregulated after BD, and the increased TCA, TDCA, and the downstream gut-derived hormone FGF15 might activate POMC neurons.